2022
DOI: 10.3389/fcvm.2022.1001072
|View full text |Cite
|
Sign up to set email alerts
|

The role of Qishen Yiqi dripping pills in treating chronic heart failure: An overview of systematic reviews and meta-analyses

Abstract: ObjectivesEvidence from systematic reviews/meta-analyses about the efficacy and safety of Qishen Yiqi (QSYQ) dripping pills in chronic heart failure (CHF) remains unclear. This study comprehensively reviewed available systematic reviews on latest evidence to provide reliable information for the clinical use of QSYQ in CHF.MethodsThe systematic review was performed on studies retrieved from six major medical databases. Eligible studies were evaluated in terms of methodological quality and quality of evidence us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Our findings of the poor methodological quality of SRs in the food field are in line with those from assessments of the methodological quality of SRs that used the AMSTAR 2 tool in other fields, including acupuncture [16,17], dentistry [18], Tai Chi [19,20], surgery [21,22], major depression in adults [23], chronic obstructive pulmonary disease [24], cardiovascular risk [25], physical activity [26], pancreatic cancer [27], chronic heart failure [28], cancerrelated fatigue [29], Alzheimer's disease [30], chronic spinal pain [31], neonatal pain [32], hip fractures [33], and atopic eczema [34]. Although the target patients or participants and interventions in those studies differed between each study, all demonstrated that the majority of SRs included had low methodological quality ("low" or "critically low").…”
Section: Findings In Contextsupporting
confidence: 82%
See 1 more Smart Citation
“…Our findings of the poor methodological quality of SRs in the food field are in line with those from assessments of the methodological quality of SRs that used the AMSTAR 2 tool in other fields, including acupuncture [16,17], dentistry [18], Tai Chi [19,20], surgery [21,22], major depression in adults [23], chronic obstructive pulmonary disease [24], cardiovascular risk [25], physical activity [26], pancreatic cancer [27], chronic heart failure [28], cancerrelated fatigue [29], Alzheimer's disease [30], chronic spinal pain [31], neonatal pain [32], hip fractures [33], and atopic eczema [34]. Although the target patients or participants and interventions in those studies differed between each study, all demonstrated that the majority of SRs included had low methodological quality ("low" or "critically low").…”
Section: Findings In Contextsupporting
confidence: 82%
“…A lack of protocol registration was the most problematic issue with the articles included in this study, and this was quite common in previous studies in other research fields [18,[23][24][25]28,30,34]. PROSPERO [36] is a well-known register of SRs, and future SR implementers must be registered.…”
Section: Findings In Contextmentioning
confidence: 99%
“…As a traditional Chinese medicine compound preparation, QSYQ has been widely used in China in the combined treatment of HF patients, owing to its efficacy of “benefiting qi and activating blood circulation”, and has achieved good therapeutic effects. A newly published reappraisal analysis of systematic reviews on QSYQ ( 82 ) points out the current lack of attention to the impact of QSYQ on mortality and readmission rates in patients with HF, even in one of the largest systematic evaluations incorporating 85 studies ( 11 ). With the popularization of the concept of heart failure vulnerable period ( 83 ) and the emphasis on the prognosis of patients with HF, more and more relevant studies have been published.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, Zhang et al (2022) proved that it mainly treats symptoms of qi deficiency and blood stasis, such as chest tightness and chest pain, shortness of breath, and spontaneous sweating. Chen L, et al (2022) found that Qishen Yiqi dripping pills mainly play an auxiliary role in the treatment of patients with coronary heart disease, and Chen W, et al (2022) demonstrated that Qishen Yiqi dripping pills could be combined with Western medicine to treat diseases such as hypertension and angina.…”
Section: Introductionmentioning
confidence: 99%